PENGARUH KUALITAS PRODUK, HARGA, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KOPI TUKU BEKASI - Jiemy Shandhiyawan Santoso (2024)
In this era, businesses have experienced rapid growth and undergone continuous transformation. One type of business that is currently popular in Indonesia is the coffee shop business. The aim of this research is to find out, prove and analyze whether product quality, price and brand image influence purchasing decisions. The population in this research is Kopi Tuku consumers who live in Bekasi. The sampling technique was purposive sampling. The sample used was 100 people. Using Partial Least Square (PLS) analysis techniques with SmartPLS 4.0 software. The results obtained show that product quality and brand image variables have a positive and significant influence on purchasing decisions, while price does not have a significant influence on purchasing decisions.